Allergic rhinitis is often undiagnosed and untreated: results from a general population study of Danish adults. (20th March 2013) - Grønhøj Larsen, Christian; Gyldenløve, Mette; Linneberg, Allan
Abstract Introduction A few earlier studies have indicated that allergic rhinitis (AR) is underdiagnosed and undertreated. Objective To assess awareness, diagnosis and treatment of AR in a general population of Danish adults. Methods Between October 2007 and June 2008, a total of 1277 consecutive participants in a Danish general population study of 18‐ to 69‐year olds were skin‐prick‐tested and asked about respiratory symptoms. AR was defined as a combination of self‐reported rhinitis symptoms and skin‐prick test reactivity against inhalant allergens. Participants reporting rhinitis symptoms completed an additional questionnaire on medication for rhinitis symptoms. Results The prevalence of AR was 23.1%. A total of 43.6% (n = 122/280) of persons with AR had not received any treatment in the previous 12 months, and only 56.6% (n = 163/288) had been given a diagnosis of hay fever by a doctor. Both AR and lower airway symptoms indicating more severe AR were reported in 48.5% (n = 143/295). These persons were significantly more likely to having received treatment in previous 12 months and a diagnosis of hay fever. Conclusion Our results support that even in an affluent country like Denmark, AR is often undiagnosed and untreated. There appears to be a need for increased awareness of AR with regard to both diagnosis and treatment.